2022
DOI: 10.52916/jmrs224086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Traumatic Vertebra and Rib Fractures

Abstract: Background: In our study, we aimed to examine the relationship between trauma-related thoracic vertebral fractures and/or rib fractures location, age and gender. Methods: Between January 1, 2020 and December 31, 2020, 100 patients with trauma-related thoracic vertebral fracture and/or rib fracture were included in the study. Rib fractures and thoracic vertebral fractures were analyzed according to age, gender, level and fracture type. The correlation between rib and vertebral fractures was investigated. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It is very important to determine the age and gender of the corpses that are not recognized in the discipline of forensic medicine. Tülüce and Altuntaş [19] reported that traumatic pneumothorax is a very important pathology that requires early intervention due to rib fractures and contusion, Ergün and Topuz [20] reported that mortality is high in fracture patients accompanied by a chest injury, Dumanli et al [7] emphasized that the coexistence of vertebral and costal fractures in trauma patients should be kept in mind, and diagnosis and treatment planning should be made accordingly. In this study, in light of the literature, criteria such as fractures or cracks, bruises and injuries in the body were reviewed while determining the first criteria to be considered in the estimation of gender and age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very important to determine the age and gender of the corpses that are not recognized in the discipline of forensic medicine. Tülüce and Altuntaş [19] reported that traumatic pneumothorax is a very important pathology that requires early intervention due to rib fractures and contusion, Ergün and Topuz [20] reported that mortality is high in fracture patients accompanied by a chest injury, Dumanli et al [7] emphasized that the coexistence of vertebral and costal fractures in trauma patients should be kept in mind, and diagnosis and treatment planning should be made accordingly. In this study, in light of the literature, criteria such as fractures or cracks, bruises and injuries in the body were reviewed while determining the first criteria to be considered in the estimation of gender and age.…”
Section: Discussionmentioning
confidence: 99%
“…40% of all trauma cases involve thoracic trauma, the third most frequent type of injury overall [3][4][5]. Thoracic injuries make up one-third of all trauma emergency and hospital admissions [5][6][7]. A tomographic image of the vertebral and rib fractures is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%